The meaning of repeated assisted reproductive technologies failures experienced of older infertile women - Hyun Jung Oh; Gisoo Shin (Frontiers in Reproductive Health)
IntroductionThe trend of older pregnant women and infertile women in South Korea, who are influencing the low birth rate, is on the rise. Older infertile women earnestly hoped for pregnancy and persisted in undergoing assisted reproductive technology multiple times. However, contrary to their wishes, they experienced failure to conceive.Materials and methodThis study is qualitative research aimed at exploring the essential meaning of the experiences of women over 35 who have faced pregnancy failure after assisted reproductive technology.ResultsThe average age of the participants in this study was 41.8 years, and they underwent an average of 5.7 assisted reproductive treatments after their infertility diagnosis. Through in-depth interviews with the participants, 120 meaningful statements were derived, which were classified into 23 themes, 9 theme clusters, and 4 categories. The four categories were “struggles and trials regarding assisted reproductive technology”, “the challenging treatment journey”, “the journey of overcoming sadness”, and “the value and happiness gained from experience”.ConclusionThe results of this study showed that infertile women over 35, despite failing to conceive after assisted reproductive technology, were able to overcome their sadness and move towards personal growth. Therefore, various methods should be sought to support the psychological growth of women undergoing assisted reproductive technology.